The Assistance of Coastal Management Group in Preservation of Mangrove Area in Ohoi Ngilngof, Southeast Maluku District - Fabian Novy Jocephs Souisa; Elizabeth Juleny Tapotubun (Institut Pertanian Bogor, 2018)
The application of science and technology (iptek) for society is one strategic way to encourage and to increase awareness about the significance of mangrove ecosystem for environment and human being. Ohoi Ngilngof is one ohoi (village) located in the Southeast Maluku District which is largely coastal area. One of the most perceived development activities that have crucial impact to the coastal environment in this region is the eviction of coastal land for expanding roads and constructing talud. This condition caused considerable pressure on the coastal area of Ohoi Ngilngof in general and particularly bring about crucial impact to the villagers. IbM activity process started with the phase of approach, and next activity are socialization, planting mangrove seedling, training (from selecting seed of mangrove seedlings to the treatment procedures) and assistance for partner of Soneratia and Rhizopora so that the output yielded from this activity is to restore the mangrove area of Mangi Ohoi Ngilngof into its original function as a place spawning, providing food, and its preservation to support the government program of Southeast Maluku District in preserving coastal areas.